Recent Morphometric Analysis of Axis Vertebra in Subjects of Indian Origin - Kaur, Jasveen; Kaur, Kamaljeet; Singh, Poonam; Kumar, Ajay (Highlights on Medicine and Medical Science Vol. 6, 2021)
Background: The axis vertebra has complex and extensive morphometric variability, and there are vital neurovascular structures nearby.Knowledge of this variability is important for neurosurgeons, orthopaedicians, otorhynologists, and other physicians who deal with spinal disorders and their consequences on a daily basis. Objective: The goalwas to evaluate various morphometric dimensions of axis vertebrae and to compare with the available data. Materials and Methods: 50 dried human axis vertebrae of Indian origin were studied in the Department of Anatomy at Dayanand Medical College and Hospital in Ludhiana. Vernier callipers, metric scales, and graph paper were used to measure various dimensions. The dimensions were measured in millimetres and statistically analysed using the paired t-test. Results: The mean of maximum anteroposterior diameter (max.APD) and maximum transverse diameter (max.TD) of Superior Articular Facet (SAF) was measured as 17.42mm±1.73 and 15.31mm±1.44 on the right side, 17.64mm±1.51 and 15.17mm±1.48 on left side. On the right and left sides, the mean distance from the SAF's lateral most edge to the midline was 22.56mm± 2.37 and 22.40mm± 2.16, respectively. On the right, the mean distance from tip of the transverse process to the midline was26.45mm± 2.85, while on the left, it was26.03mm± 2.64. The mean Height of Dens was measured as 13.83mm ± 1.52, mean Width of Dens as 9.57mm ± 0.85. Width of Pedicle was measured as 10.52mm ± 1.99 and 10.61mm ± 1.67on right and left sides, respectively. Conclusion: Knowing these dimensions can help with safe osseous fixation planning.